A Positive Depression Screen Is Associated with Emergency Medicine Resident Burnout and Is not Affected by the Implementation of a Wellness Curriculum - Kelly Williamson (eScholarship Publishing, University of California, 2021)
Introduction: While burnout is occupation-specific, depression affects individuals comprehensively. Research on interventions for depression in emergency medicine (EM) residents is limited. Objectives: We sought to obtain longitudinal data on positive depression screens in EM residents, assess their association with burnout, and determine whether implementation of a wellness curriculum affected the rate of positive screens. Methods: In February 2017, we administered the Maslach Burnout Inventory and the Primary Care Evaluation of Mental Disorders Patient Health Questionnaire two-question depression screen at 10 EM residencies. At five intervention sites, a year-long wellness curriculum was then introduced while five control sites agreed not to introduce new wellness initiatives during the study period. Study instruments were re-administered in August 2017 and February 2018. Results: Of 382 residents, 285 participated in February 2017; 40% screened positive for depression. In August 2017, 247/386 residents participated; 27.9% screened positive for depression. In February 2018, 228/386 residents participated; 36.2% screened positive. A positive depression screen was associated with higher burnout. There were similar rates of positive screens at the intervention and control sites. Conclusion: Rates of positive depression screens in EM residents ranged between 27.9% and 40%. Residents with a positive screen reported higher levels of burnout. Rates of a positive screen were unaffected by introduction of a wellness curriculum.